Effect of Diet Complexity and Specialty Protein Source on Nursery Pig Performance - A. M. Jones; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 720 nursery pigs (PIC C-29 × 359, initially 12.5 lb BW) were used in a 42-d growth trial to determine the effects of diet complexity and specialty soy protein source on nursery pig performance. Pigs were allotted by BW and sex, and randomly assigned to 1 of 6 dietary treatments in a 2 × 3 factorial arrangement with main effects of diet complexity (complex vs. simple) and specialty protein source (fish meal, HP 300, or HP 800). The HP 300 and HP 800 are two different enzymatically treated soy products manufactured and sold by Hamlet Protein (Findlay, OH). Experimental diets were fed in two phases (Phase 1 was budgeted at 5 lb per pig and Phase 2 was fed thereafter until d 21) with a common diet fed for 3 wk following the experimental diets. No interactions were observed between diet complexity and protein source for growth performance for any phase or overall. From d 0 to 7, pigs fed the complex diet had a tendency for improved ADG (P = 0.078) and d 7 BW (P = 0.053) compared to pigs fed the simple diet. There was no difference in performance observed from d 7 to 21; however, for the overall treatment feeding period (d 0-21), pigs fed the complex diets had improved F/G (P = 0.037) compared to pigs fed the simple diets. During the Phase 3 common diet feeding period (d 21 to 42), no differences were observed between pigs previously fed different diet complexity or protein sources. Overall (d 0 to 42), no differences in growth performance were found between treatments. For economics, pigs fed a simple diet tended to have greater IOFC (P = 0.055). Feed cost per pound of gain was lower (P = 0.002) for pigs fed diets with HP 300 and HP 800 compared to those fed diets with fish meal. In summary, this study suggests that the differences in diet complexity used in this study had minor impacts on growth performance during the phases in which they were fed but not overall. Furthermore, the three specialty protein sources used in this study resulted in similar growth performance.
Keywords: diet complexity; nursery pig; protein sources